Does Denomination Influence Pastors’ Readiness for Retirement? Evidence From Southern California Pastors - Paeng, Seongcheol; Park, Daniel (Journal of Accounting and Finance, 2024)
This study explores retirement issues among pastors. Recent studies indicate that many pastors work past retirement age due to financial unpreparedness. We examine whether retirement preparedness and job satisfaction vary by denomination. We focus on three key retirement concerns: retirement comfort, overall job satisfaction, and financial satisfaction. Using survey data from Southern California pastors, we find that Methodist pastors are more prepared for retirement compared to others, while Presbyterian pastors are less content with their roles than other denominations. However, denomination does not significantly affect the financial satisfaction of pastors.